USING INTERACTIVE LECTORA INSPIRE SOFTWARE TO IMPROVE LEARNING OUTCOMES DURING PANDEMIC COVID-19 - Uus Toharudin (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2023)
One of the obstacles to the development of interactive learning media is the lack of mastery of interactive media development technology by teachers, so that the development of interactive learning materials with computers is not optimal. The purpose of this study was to test the effectiveness of interactive learning on motion system material assisted by the Lectora inspire software in improving learning outcomes. Using the pre-experimental method, this study involved 36 participants. Data collection techniques using test questions and questionnaires. Data analysis used the Wilcoxon test. The results of this study indicate that the effectiveness of using interactive Lectora Inspire software on motion material can improve student learning outcomes with a p-value of 0.006 where the p-value < α = 0.05. Thus the application of the Lectora Inspire software can be used as a solution, especially in online learning as a form of learning innovation.